2010
DOI: 10.1097/ogx.0b013e31821285bf
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Pregnancy After Primary Breast Carcinoma in Young Women: A Meta-Analysis to Overcome Bias of Healthy Mother Effect Studies

Abstract: After completing this CME activity, physicians should be better able to assess the effect pregnancy has on long-term survival in primary breast cancer patients under age 45; counsel patients on the safety of pregnancy after breast cancer diagnosis and treatment; and interpret how pregnancy may be associated with improved breast cancer survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(43 citation statements)
references
References 22 publications
2
36
0
5
Order By: Relevance
“…After considering the potential for such a bias in the matched controls, ten studies were eligible, and nine contained data appropriate for analysis. Overall survival was statistically higher among patients who became pregnant than among those who did not, showing that pregnancy occurring at least 10 months after a bca diagnosis does not jeopardize prognosis and might even confer a significant survival benefit 60 . The same results were also recently reported in a third meta-analysis studying the safety of pregnancy after surgical treatment for bca.…”
Section: Meta-analysismentioning
confidence: 93%
“…After considering the potential for such a bias in the matched controls, ten studies were eligible, and nine contained data appropriate for analysis. Overall survival was statistically higher among patients who became pregnant than among those who did not, showing that pregnancy occurring at least 10 months after a bca diagnosis does not jeopardize prognosis and might even confer a significant survival benefit 60 . The same results were also recently reported in a third meta-analysis studying the safety of pregnancy after surgical treatment for bca.…”
Section: Meta-analysismentioning
confidence: 93%
“…A meta-analysis designed to correct for the "healthy mother effect" included over 1000 women with pregnancy after breast cancer diagnosis and over 13000 health-matched controls. This study noted improved survival in women who became pregnant after breast cancer treatment as compared to those who did not, hazard ratio 0.51 [95% confidence interval (CI), 0.42-0.62] suggesting that pregnancy at least 10 mo post breast cancer treatment in women < 45 years does not adversely affect prognosis and may in fact significantly improve survival [60] . About 50% of women can lactate after breast cancer therapy, but breast milk volume tends to be reduced [61] .…”
Section: Management Of Vulvovaginal Atrophy In the Breast Cancer Survmentioning
confidence: 96%
“…Estrogen-receptor status does not impact breast cancer recurrence with pregnancy [59] . Initial studies noting improved outcome in women who become pregnant after breast cancer were attributed to better baseline status in women who chose pregnancy, the so-called "healthy mother effect" [60] . A meta-analysis designed to correct for the "healthy mother effect" included over 1000 women with pregnancy after breast cancer diagnosis and over 13000 health-matched controls.…”
Section: Management Of Vulvovaginal Atrophy In the Breast Cancer Survmentioning
confidence: 99%
“…Several meta-analyses have also reached to the same conclusion that pregnancy subsequent to breast cancer therapy does not impact the recurrence rate or overall survival (14)(15)(16). In an attempt to overcome a possible bias of a healthy mother effect a meta-analyses of nine studies comprising 1089 pregnancies and 13051 matched controls that had taken this in consideration found that a pregnancy occurring at least 10 months after diagnosis may result in a survival benefit (HR 0.51 95% CI: 0.42-0.62) (15).…”
Section: Pregnancy After Breast Cancer Treatmentmentioning
confidence: 99%